Teachers’ Moral Intelligence: A Scale Adaptation into Turkish and Preliminary Evidence - Mustafa Toprak* (European Journal of Educational Research, 2018)
The purpose of this work is to adapt the existing Moral Competency Index (MCI) developed by Lennick and Kiel in a sample of teachers. The validated Turkish version of MCI is based on the item pool of the original MCI with a slight adaptation of the items to fit the context of teacher leadership. The translated form was administered to 773 teachers in Gaziantep city. Exploratory factor analysis, Cronbach’s Alpha and Split-half reliability, and item analysis were performed through SPSS, while the first and second order confirmatory factor analyses were performed through AMOS. Results showed that adapted Turkish form of MCI (Ogretmen Ahlaki Yeterlik Olcegi) is reliable and valid, and the four-dimensional original factorial structure (integrity, responsibility, forgiveness, and compassion) was confirmed and maintained. Finally, multiple regression analyses were performed. Results showed that female teachers have higher levels of moral competencies in the dimensions of integrity and forgiveness. Also, as teachers’ age increases, their general moral competency scores increase in the dimensions of integrity, responsibility, and compassion.